Characterization of Soil Physical Properties Based on Selected Parameters at the Experimental Farm of the Faculty of Agriculture, University of Jember - Purnama Sari, Retno; Hidayatulloh, Mukhamad Wildan; Romadhon, Muhammad Rizal; Basuki, Basuki (Universitas Jember, 2026)
Soil functions as a medium for plant growth, a reservoir of air and nutrients, and a habitat for various soil organisms. The effectiveness of these functions depends largely on the properties of the soil, which are generally classified into physical, chemical, and biological properties. Among other things, the physical properties of the soil play an important role in regulating soil processes related to air movement, aeration, root penetration, and the availability of nutrients for plants. This research aims to characterize the physical properties of soil based on selected parameters at the Experimental Farm, Faculty of Agriculture, University of Jember. Soil samples were collected and analyzed at the Soil Physics and Conservation Laboratory from September to November 2025. Parameters observed included soil water content, bulk density, particle density, porosity and soil texture using standard laboratory methods. The research results showed that the average soil water content was 63.8%. The bulk density ranged from 0.84 to 0.94 g/cm³ with an average of 0.88 g/cm³. Particle density ranged from 2.24 to 2.46 g/cm³ with an average of 2.35 g/cm³. The average porosity was 62.5%, indicating a high proportion of pore space that supports air retention and aeration. Soil texture analysis shows that the soil is dominated by clay and clay loam textures, which contribute to the high air holding capacity due to the presence of micropores